KETERAMPILAN MANAJEMEN KELAS OLEH GURU ILMU PENGETAHUAN ALAM - Dita Kurniawati (Jurnal Tawadhu, 2024)
The aim of classroom management is to create a comfortable, conducive and interactive classroom atmosphere so that the material presented and the objectives implemented can be achieved. This research uses descriptive qualitative research methods. Descriptive qualitative research was conducted to explain existing research without manipulating the data variables studied. Classroom management can include two things, namely 1) physical, such as classroom arrangement, ventilation and lighting, layout of student desks and chairs, teacher desks, classroom support furniture, and other learning tools in the classroom. 2) student management, student behavior, motivation and interest in learning, attention in receiving learning material, especially natural sciences, and passion for learning. Factors supporting classroom management skills by Natural Science teachers are teachers, students and supporting facilities. Factors inhibiting classroom management skills are teachers who cannot pay attention to all students and do not have the ability to carry out the teaching and learning process. Students who do not focus on paying attention to the material presented by the teacher can be an inhibiting factor in classroom management.